(3UMjM GHf MHGfs - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s
(3ChdgG (B:s
(3jHJOF ef GdfhY GdSGOS hGdJSYjf Edi PcQ oeYGhjI GHf CHj SajGf s
(3GdfSNI HgG MhGTs
(3ef fSNI KGfjIs
(3YdjgG SeGYGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs